2008
DOI: 10.1158/1055-9965.epi-08-0411
|View full text |Cite
|
Sign up to set email alerts
|

International Lung Cancer Consortium: Pooled Analysis of Sequence Variants in DNA Repair and Cell Cycle Pathways

Abstract: Background: The International Lung Cancer Consortium was established in 2004. To clarify the role of DNA repair genes in lung cancer susceptibility, we conducted a pooled analysis of genetic variants in DNA repair pathways, whose associations have been investigated by at least 3 individual studies. Methods: Data from 14 studies were pooled for 18 sequence variants in 12 DNA repair genes, including APEX1, OGG1, XRCC1, XRCC2, XRCC3, ERCC1, XPD, XPF, XPG, XPA, MGMT, and TP53. The total number of subjects included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 32 publications
(24 reference statements)
3
87
1
Order By: Relevance
“…Through literature search and selection based on the inclusion criteria, 39 studies were found, but only 22 studies met our inclusion criteria, as listed in Table 1. Seventeen studies were excluded for the following reasons: five studies did not contain exact genotype distribution information; (17)(18)(19)(20)(21) four studies were reviews; (22)(23)(24)(25) four studies were not case-control studies; (26)(27)(28)(29) and in three studies, (30)(31)(32) genotype distributions in control population deviated from the Hardy-Weinberg equilibrium. Furthermore, one study of bladder cancer (33) in which the variant allele frequency was extremely lower than expected, which may reflect wrong allele counting or poor genotyping quality, was also excluded from our meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Through literature search and selection based on the inclusion criteria, 39 studies were found, but only 22 studies met our inclusion criteria, as listed in Table 1. Seventeen studies were excluded for the following reasons: five studies did not contain exact genotype distribution information; (17)(18)(19)(20)(21) four studies were reviews; (22)(23)(24)(25) four studies were not case-control studies; (26)(27)(28)(29) and in three studies, (30)(31)(32) genotype distributions in control population deviated from the Hardy-Weinberg equilibrium. Furthermore, one study of bladder cancer (33) in which the variant allele frequency was extremely lower than expected, which may reflect wrong allele counting or poor genotyping quality, was also excluded from our meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Four publications were excluded because of meta-analysis, control group had cancer patients or not published in English. Finally, 26 full-text articles with eligibility were included in this meta-analysis (Smith et al, 2003;Huang et al, 2006;Mechanic et al, 2006;Moreno et al, 2006;Crew et al, 2007;Jorgensen et al, 2007;Chang et al, 2008;Hung et al, 2008;McWilliams et al, 2008;Rajaraman et al, 2008;Abbasi et al, 2009;Han et al, 2009;Joshi et al, 2009;Agalliu et al, 2010;Rajaraman et al, 2010;Doherty et al, 2011;Krupa et al, 2011;Smith et al, 2011;Gil et al, 2012;Yu et al, 2012;Cheng et al, 2013;Santos et al, 2013;Wang et al, 2013;Wyss et al, 2013;Kohlhase et al, 2014;Steck et al, 2014). The flow chart which reflected the details of article selection was presented in Figure 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Activity in the repair of 8-hydroxyguanine is greater with the hOGG1-Ser326 protein than the hOGG1-Cys326 protein, 5 and the possible contribution of this locus to the risk of a variety of human cancers has been reported. 6 A number of studies [7][8][9][10][11][12][13][14] and systematic approaches [15][16][17] have examined the role of the Ser326Cys polymorphism in lung cancer susceptibility. One meta-analysis showed that the overall odds ratio (OR) of homozygotes for the hOGG1-326Cys allele against those for the hOGG1-326Ser allele was 1.24 (95% confidence interval (CI)¼1.01-1.53), suggesting that the locus is involved in susceptibility to overall lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…15 A recent pooled analysis from the International Lung Cancer Consortium involving a substantial number of cases and controls showed a suggestive association for this polymorphism in Caucasians. 16 One question that remains unanswered is whether the impact of rs1052133 differs according to histological subtype of lung cancer.…”
Section: Introductionmentioning
confidence: 99%